Hydrogen segregation near a crack tip in nickel. (15th March 2021) - Drexler, A.; He, S.; Pippan, R.; Romaner, L.; Razumovskiy, V.I.; Ecker, W.
Abstract: The effect of severe elastic straining of interstitial lattice sites in front of a crack tip in nickel is investigated. There the volumetric strains can reach values close to the theoretical limit of around 20%. Segregation energies of volumetrically strained octahedral sites were calculated by means of the density functional theory (DFT) and were compared with the segregation energies of hydrogen trapped at the free surface and other microstructural defect sites. The calculations revealed a strong effect of volumetric straining on hydrogen segregation in the first atomic layers ahead the crack tip, which is comparable to hydrogen segregation at grain boundaries or vacancies. According to the calculations, the hydrogen distribution in the process zone is strongly inhomogenous with full occupation of, both, free surface sites and volumetric strained sites in the first atomic layers in front of the crack tip. Graphical Abstract: Image, graphical abstract